Evaluation of Dual Tobacco Smoking (Water Pipe and Cigarettes) and Associated Factors in Adults in Tehran - Hessami, Zahra (Tanaffos, 2016)
BACKGROUND: Concurrent use of tobacco products such as cigarettes and water pipes may be associated with increased risk of nicotine dependence and smoking-related complications. Accurate statistics are not available regarding the prevalence of water pipe use or concurrent use of cigarettes and water pipe in the Iranian population. Thus, this study sought to assess the prevalence of concurrent use of cigarettes and water pipes and their related factors in Iran. MATERIALS AND METHODS: This cross-sectional study was conducted on Tehran residents over 15 years of age, who were selected via cluster, multi-stage randomized sampling, from different geographical districts of Tehran between November and December 2014. The data were collected using the water pipe section of the Global Adult Tobacco Survey (GATS) questionnaire. RESULTS: A total of 1,830 individuals participated in this study, 243 (13.3%) of which exclusively used water pipes, 76 (4.2%) used both cigarettes and water pipes, and 120 (6.6%) exclusive smoked cigarettes. Of those who used both cigarettes and water pipes, 86.8% were men and 13.2% were women (P < 0.001). The mean age of those who only used water pipes was 28.01 ± 8.7 years while the mean age of those who used both water pipes and cigarettes was 33.1 ± 1.1 (P < 0.001). Male sex (adj. OR: 3.8) and older age (adj. OR: 1.06) increased the odds of using both tobacco products. CONCLUSION: The prevalence of concurrent use of cigarettes and water pipes and that of exclusive water pipe use were 4.2% and 13.3%, respectively. The prevalence of exclusive cigarette smoking was 6.1%. Those who smoked both cigarettes and water pipes had a higher mean age than those who exclusively used water pipes and they were mostly men. Among those who used cigarettes and water pipes, the mean age at which they began using water pipes was lower than the mean age at which they began smoking cigarettes. In other words, dual smokers started water pipe smoking sooner than cigarette smoking. Future studies with different methodologies are required to further scrutinize the relationship between water pipe and cigarette smoking. Smoking cessation programs must specifically target dual smokers.